Clinical and pathophysiological delineation of musculocontractural Ehlers—Danlos syndrome caused by dermatan sulfate epimerase deficiency (mcEDS‐DSE): A detailed and comprehensive glycobiological and pathological investigation in a novel patient. Issue 12 (23rd July 2022) - Minatogawa, Mari; Hirose, Takuya; Mizumoto, Shuji; Yamaguchi, Tomomi; Nagae, Chiai; Taki, Masashi; Yamada, Shuhei; Watanabe, Takafumi; Kosho, Tomoki
Abstract: Musculocontractural Ehlers–Danlos syndrome caused by dermatan sulfate epimerase deficiency (mcEDS‐ DSE ) is a rare connective tissue disorder. This is the first report describing the detailed and comprehensive clinical and pathophysiological features of mcEDS‐ DSE . The patient, with a novel homozygous nonsense variant (NM_013352.4:c.2601C>A:p.(Tyr867*)), exhibited mild skin hyperextensibility without fragility and small joint hypermobility, but developed recurrent large subcutaneous hematomas. Dermatan sulfate (DS) moieties on chondroitin sulfate/DS proteoglycans were significantly decreased, but remained present, in skin fibroblasts. Electron microscopy examination of skin specimens, including cupromeronic blue‐staining to visualize glycosaminoglycan (GAG) chains, revealed coexistence of normally assembled collagen fibrils with attached curved GAG chains and dispersed collagen fibrils with linear GAG chains from attached collagen fibrils across interfibrillar spaces to adjacent fibrils. Residual activity of DS‐epi1, encoded by DSE, and/or compensation by DS‐epi2, a minor homolog of DS‐epi1, may contribute to the mild skin involvement through this "mosaic" pattern of collagen fibril assembly.